2007
DOI: 10.1057/palgrave.jt.5750063
|View full text |Cite
|
Sign up to set email alerts
|

M-politics: Credibility and effectiveness of mobile political communications

Abstract: New communication technologies and, in particular, SMS ( Short Message Service ) -that is, undersized text messages sent to a mobile phone by a computer or by another mobile deviceoffer political parties and candidates an innovative tool for communicating with their actual and prospective voters. The present study evaluates both credibility and its effects on the voting intention of SMS political communication (ie mobile-politics , M-Politics ), by considering credibility as a characteristic ascribed to SMS. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…It also provides evidence on the relevance of contextual online factors, particularly in the growing research stream of mobile marketing. Previous studies in mobile marketing research have considered the credibility and effectiveness of political communication (Prete, ), mobile phone adoption (Muk, ), or consumers’ perceptions and attitudes toward mobile marketing (Roach, ). As far as one can tell from the literature, this study represents the first attempt to examine the role of blue lighting in driving individuals’ purchasing intentions during mobile shopping.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…It also provides evidence on the relevance of contextual online factors, particularly in the growing research stream of mobile marketing. Previous studies in mobile marketing research have considered the credibility and effectiveness of political communication (Prete, ), mobile phone adoption (Muk, ), or consumers’ perceptions and attitudes toward mobile marketing (Roach, ). As far as one can tell from the literature, this study represents the first attempt to examine the role of blue lighting in driving individuals’ purchasing intentions during mobile shopping.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…Besides Web communications, politicians around the globe are increasingly using mobile phone technology for political purposes (see e.g. Prete, 2007;Hermanns, 2008). Campaigners have realized the potential of text messaging and are using targeted SMS messages with information about candidates and their programmes in order to reach more citizens, mobilize support and encourage supporters to cast their votes to elections.…”
Section: Digital Media In a Political Contextmentioning
confidence: 99%
“…According to this view, Lammers, Galinsky, Gordijn, and Otten () showed that powerful subjects are more likely to be more morally hypocritical than those lacking in power, highlighting a correlation between the holding of power and hypocrisy. Political hypocrisy is related to other constructs, such as political credibility—the degree to which citizens rely on their political communicators and consider them trustworthy, attractive, and expert (Prete, )—and political cynicism—which concerns the politicians' integrity and effectiveness in governing (Berman, ).…”
Section: Political Hypocrisymentioning
confidence: 99%